2018
DOI: 10.1002/pola.29002
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer along a sequence controlled hybrid polymer

Abstract: The present work provides an ideal model for intra‐chain energy transfer study in conjugated polymer through shielding the polymer backbone by using bulky polyhedral oligomeric silsesquioxanes (POSS). POSS provides a circumference shielding of the polymer backbone to prevent closed packing of the polymer chains, allowing the intra‐chain energy transfer dominating in large concentration range. Bi‐functional POSS (B‐POSS) is specially designed to separate donor (fluorene) and acceptor (benzothiadiazole) within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The addition of POSS was reported to have significant effect in retarding the random breakage of the polymer backbone as well [ 38 ]. Comparison of the length of PCL in the hybrids with similar ratio of B-POSS indicated that PCL may also help to enhance thermal stability of the PUs because T d also depends on the molecular weight (M n ) of the polymer drastically [ 36 ], and the long-chain oligomers with POSS could enhances the thermal stability of the polyurethane by better dispersion [ 25 , 26 , 27 , 29 ]. The copolymer and neat PU exhibited similar TGA profiles, indicating that the incorporation of B-POSS had no significant effect on the degradation mechanism of the PUs backbone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of POSS was reported to have significant effect in retarding the random breakage of the polymer backbone as well [ 38 ]. Comparison of the length of PCL in the hybrids with similar ratio of B-POSS indicated that PCL may also help to enhance thermal stability of the PUs because T d also depends on the molecular weight (M n ) of the polymer drastically [ 36 ], and the long-chain oligomers with POSS could enhances the thermal stability of the polyurethane by better dispersion [ 25 , 26 , 27 , 29 ]. The copolymer and neat PU exhibited similar TGA profiles, indicating that the incorporation of B-POSS had no significant effect on the degradation mechanism of the PUs backbone.…”
Section: Resultsmentioning
confidence: 99%
“…The second merit is the biocompatibility and non-toxicity of POSSs [21,22,23,24]. Moreover, according to our previous results, not only could POSS enhance thermal stability [25,26], but it could also strengthen the mechanical properties [27] and retain the optical stability of the materials [28,29] due to its special composition and cage-liked nanostructure. In addition, POSS can be introduced into a polymer matrix by using covalently bonding as a pendent side group [30,31,32,33] or as end groups [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…To synthesize high-performance polymers, POSSs are often functionalized with aromatic groups [81][82][83][84]. Seino et al [69] reported that the reaction between B-POSS and diynes resulted in the formation of linear polymers via hydrosilylation polymerization.…”
Section: Aromatic Ring Functionalized Possmentioning
confidence: 99%
“…[23][24][25] The produced silicones can be used to modulate the mechanical performance while maintaining or optimizing the optical properties of polymers. [26,27] Additionally, primary amino groups are widely used to enhance the affinity of materials to heavy metals [28,29] because of the strong coordination and electron-donating interaction between them. [30,31] Therefore, polyaminosiloxane (PAS) was designed and grafted onto the sponge through a nucleophilic reaction between the amine and glutaraldehyde (GLA).…”
Section: Introductionmentioning
confidence: 99%